2017
DOI: 10.12816/0042578
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescription in Ophthalmology

Abstract: Background: Drug prescription studies provide a pharmacoeconomic basis for making evidence-based health-care decisions. In ophthalmology practice, rational prescribing shows a vital role in decreasing the ocular disease burden. Purpose: The purpose of the study was to inspect the drug consumption pattern in ophthalmology department of King Abdulaziz hospital in KSA. Materials and Methods: A prospective, cross-sectional study was conducted for a period of 3 months. The prescriptions for all consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Out of 272 patients, 148 (54%) were female and 124 (46%) were male. This result was similar to studies carried out by Rawah MA et al 14 and Prathap SA et al 15 and on the contrary, studies done by Slathia A et al 16 and Dhami DB et al 17 showed that men were more prone to Ocular diseases than women. Hence these findings conclude that the eye diseases are not usually sex linked.…”
Section: Discussionsupporting
confidence: 91%
“…Out of 272 patients, 148 (54%) were female and 124 (46%) were male. This result was similar to studies carried out by Rawah MA et al 14 and Prathap SA et al 15 and on the contrary, studies done by Slathia A et al 16 and Dhami DB et al 17 showed that men were more prone to Ocular diseases than women. Hence these findings conclude that the eye diseases are not usually sex linked.…”
Section: Discussionsupporting
confidence: 91%